Occupational diseases among farmers in Poland - Neonila Szeszenia-Dąbrowska; Beata Świątkowska; Urszula Wilczyńska (Nofer Institute of Occupational Medicine, 2016)
Background: The study's objective is to present epidemiological situation concerning the incidence of occupational diseases among farmers in Poland. Material and Methods: All 3438 cases of occupational diseases diagnosed among farmers and obligatorily reported to the Central Register of Occupational Diseases (covering all the national territory and all the cases of occupational diseases diagnosed in Poland after 1970) over the years 2000-2014 were subjected to analysis. Results: The annual incidence in the analyzed period ranged 5-14 per 100 000 farmers. The analysis showed that about 90% of pathologies were induced by the biological agents. Almost every third pathology due to biological agents had allergic origin. Infectious and parasitic diseases accounted for 62% of the cases. Among them the diseases carried by ticks (93%) - borreliosis (85.8%) and tick-borne encephalitis (7.2%) were the most frequent ones. The age of farmers, in the case of whom bronchial asthma and allergic rhinitis were diagnosed, was significantly higher than the age of remaining employees of the national economy, in which these occupational diseases were recognized. Conclusions: The study indicates the necessity to introduce periodic health examinations programs focusing on agricultural workers to monitor health and well-being and improve working conditions and the working environment. Med Pr 2016;67(2):163-171